Analysis Of Power Distribution System Reliability Using System Average Interruption Duration Index ( SAIDI) and System Average Interruption Frequency Index ( SAIFI) On Feeder KR04 - Irham Amando Lubis; Dino Erivianto; Zuraidah Tharo (International Journal of Economic, Technology and Social Sciences (Injects), 2024)
This study aims to analyze the reliability of the electricity distribution system using the SAIDI (System Average Interruption Duration Index) and SAIFI (System Average Interruption Frequency Index) in KR04 Sungai Mas. The results of the analysis show that frequent disruptions affect the reliability of the system, which has a direct impact on the level of customer satisfaction with electricity distribution services. The SAIDI value is 0.15235 hours/customer and SAIFI of 0.00017 times/customer in 2024 indicates that the system is not yet fully reliable. Reliability improvements are made through maintenance of network components, installation of lightning rods, and optimization of tree pruning. This study emphasizes the importance of reducing the frequency and duration of disruptions to improve system reliability and customer satisfaction.